Media coverage of DeepFake disinformation: An analysis of three South-Asian countries - Sunvy, Ahmed Shafkat; Reza, Raiyan Bin; Imran, Abdullah Al (Informasi, 2023)
A lot of people are concerned about DeepFakes in modern society. Despite its wide range of uses, DeepFakes has gotten little public recognition. The main goal of this research is to analyze DeepFakes and their originators, as well as their potential and risks. We analyzed 203 news articles from 16 media outlets in Bangladesh, India, and Pakistan to achieve our goal. The extracted news had been categorized under threat, prevention and entertainment centric news. It has been revealed after analyzing DeepFake related news from the leading English daily of these countries that more than 50% news of Pakistani newspapers related to DeepFake was on the threat of this heinous technology. On the other hand, one third news of Indian and Bangladeshi newspapers was on this regard. The widespread broadcast of misleading information through media outlets might boost their legitimacy and reception for a short time but slowly and steadily smear their good name. This study also highlights the significant role media professionals have in spreading disinformation about the people and topics they cover.